A Application of the Project Based Learning (PjBL) Model to the ability to write biographical texts at SMAN2 Tapung Hilir: Penerapan Model Project Based Learning (PjBL) Terhadap Kemampuan Menulis Teks Biografi di SMAN 2 Tapung Hilir - Hani Khoirunnisa; Desi Sukenti (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Higher-order thinking skills are mastered by students as a guide in implementing creative and critical thinking learning. High-level thinking is seen as the ability to think critically to develop relationships through the most basic brain processes. To overcome the problem of students' lack of ability in learning to write biographical texts, researchers assess the application of the Project Based Learning (PjBL) learning model, because this learning model is able to complete problem of higher order thinking skills at SMAN 2 Tapung Hilir. This study is a type of quantitative study. By using an experimental model. The collection technique hereby uses the test and questionnaire methods. Data analysis used quantitative descriptive analysis. Based on the study conducted, it was found that the t-count > t- table value was -2.428 > 1.665 and the sig value was 0.001 <0.1. This shows that this research can prove that there is an influence of the Project Based Learning (PjBL) Model on the ability to write biographical texts at SMAN 2 Tapung Hilir.